Education on Hadith Understanding as an Effort to Resolve Conflicts Between Islamic Organizations in Wates-Kediri - Khamim, Khamim; Masrur, Imam; Hariono, Duwi; Soroni, Mohd. Khafidz (Madania: Jurnal Kajian Keislaman, 2024)
Maintaining and encouraging religious moderation in Muslims is a difficult undertaking. The main challenge comes from within the Muslim community, namely the emergence of intolerance towards different understandings or practices among Islamic Community Organizations (ORMAS). This study examines the problem of intolerance in understanding religion and religious practices that occurs between Islamic mass organizations in Duwet Village, Wates District, Kediri Regency. The aim is to find out the sources of intolerance and make measures to solve it. This is carried out to foster an objective scientific atmosphere and a moderate religious life, which entails understanding and accepting that diversity and differences are unavoidable. This study employs a phenomenological approach in which data is obtained through interviews and observations. The results of the study show that intolerance between mass organizations in Duwet Village occurs due to two things: first; differences in understanding the hadith and second; the existence of group/group fanaticism. Differences in understanding occur due to the lack of literacy about the hadith and how to understand it correctly. Meanwhile,fanaticism in a group or organization makes the hadith not studied objectively. The first problem was solved by means of hadith literacy education initiated by the Duwet Village Mosque and Musholla Communication Forum (FKTM2), namely with discussion forums and learning about hadith. Furthermore, the second problem is solved by instilling moderation values through a gathering forum in Wates district, Kediri Regency. Menumbuhkan dan merawat moderasi beragama di kalangan umat Islam bukanlah hal yang mudah. Tantangan terbesarnya justru dari dalam umat Islam itu sendiri, yaitu terjadinya intoleransi terhadap paham atau amalan di kalangan organisasi masyarakat Islam (ORMAS). Penelitian ini mengkaji tentang problem intoleransi pemahaman agama dan amalan keagamaan yang terjadi antar Ormas Islam di Desa Duwet Kecamatan Wates Kabupaten Kediri. Tujuannya untuk mengetahui sebab-sebab terjadinya problem intoleransi dan upaya penyelesaiannya. Hal ini dilakukan dalam rangka menumbuhkan iklim ilmiah yang obyektif dan mewujudkan kehidupan beragama yang moderat yakni mengakui dan menyadari bahwa keragaman dan perbedaan adalah keniscayaan. Penelitian ini menggunakan pendekatan fenomenologis di mana data-datanya diperoleh melalui wawancara dan observasi. Hasil penelitian menunjukkan bahwa intoleransi antar ORMAS di Desa Duwet terjadi karena dua hal: pertama; adanya perbedaan pemahaman hadis dan kedua; adanya fanatisme kelompok/golongan. Perbedaan pemahaman terjadi karena minimnya literasi tentang hadis dan bagaimana cara memahaminya dengan benar. Sedangkan fanatisme kelompok atau golongan menjadikan hadis tidak dikaji secara obyektif. Untuk persoalan pertama diselesaikan dengan cara edukasi literasi hadis yang digagas oleh Forum Komunikasi Masjid dan Musholla (FKTM2) Desa Duwet yakni dengan forum-forum diskusi dan pembelajaran mengenai hadis. Sedangkan persoalan kedua diselesaikan dengan cara menanamkan nilai-nilai moderasi melalui forum silaturahmi umat Islam kecamatan Wates Kabupaten Kediri.